Educating Deaf Children in an Inclusive Setting in Kenya: Challenges and Considerations - and Adoyo, Peter Oracha (2007)
Educators of the deaf have been of the view that placement of deaf students in classrooms with their hearing peers often may not be conducive to their social and academic development. This is because the two groups often experience difficulties in communication with each other and that such difficulties often include loneliness, rejection and social isolation. These experiences as observed by the educators do not promote social and academic development. This paper discusses perspectives on inclusive education in general and the deaf in particular. Challenges encountered in placing the deaf child in an inclusive classroom are highlighted and possible solutions to the administrators and teachers are suggested.